THE CONTRIBUTION OF POSITIVE THINKING SKILLS TO STUDENTS' LEARNING OUTCOMES: KONTRIBUSI KETERAMPILAN BERPIKIR POSITIF TERHADAP HASIL BELAJAR SISWA - Baliana, (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
Positive thinking is one of the factors that influence student learning outcomes. This is because students' negative assumptions result in students not trying to solve the problem properly. Therefore, this research was conducted to see the contribution of positive thinking to student learning outcomes and how to grow it. This research was conducted at MAN 2 Soppeng involving 24 students of class XI. Data was collected by giving points and interview guidelines to measure students' positive thinking, while the learning outcomes data were obtained through student exam results. Interviews were conducted with 3 students who were considered to represent each category of positive thinking level. By using the regression analysis test it is known that positive thinking has a significant effect by contributing 35.3% so this also needs to be a concern in the learning process so that students can optimize their abilities. The ability to think positively can be improved in various ways, such as by creating a good environment, setting goals, applying appropriate learning models, and utilizing learning media. Therefore, each element plays an important role in optimizing students' abilities.